KONTRIBUSI MOTOR ABILITY DAN KONSENTRASI TERHADAP KEMAMPUAN PENGUASAAN KATA HEIAN YODAN KARATEKA LEMKARI DOJO ANGKASA LANUD PADANG - Arie Asnaldi (Jurnal MensSana, 2019)
The problem in this research is based on observations in the field, there is still a lack of some aspects of the physical conditions that affect the Heian said yodan conducted by karate dojo LEMKARI Space Lanud Padang. Presumably there are several factors that affect the Kata heian yodan, among these factors is the motor ability and concentration. This study aims to explain the contribution of the motor ability and concentration on the mastery of the Kata heian yodan. This research method is quantitative method using data analysis techniques regression and correlation, either single or double. The population in this study is the karateka LEMKARI Dojo Space Lanud Padang enrolled in training, totaling 52 people, with a sample of 32 people were taken by purposive sampling that karateka daughter alone. Measurements ability using Barrow motor data Motor Ability Test were then processed using the formula lewis, to the concentration data using Grid Concentration Test. For mastery of data pegukuran Kata Heian yodan with Rule Of Competition World Karate Federation of the Executive Board of Forki with Kata Scoring Form of Free Game FKTI-INKAI. Based on data analysis results: (1) The components of motor abilities contributed 17.39% to the mastery of the kata heian yodan; (2) Components of concentration contributed 12.47% to the mastery of the word kata heian yodan; (3) Taken together the motor ability and concentration contributed 25.17% to the Heian yodan word mastery, and the remaining percentage is influenced by other factors. Based on these results, we can conclude that the motor ability and concentration to contribute jointly towards mastery of the kata heian yodan.